Eco-fascism: an oxymoron? Far-right nationalism, history, and the climate emergency - Conversi, Daniele (Frontiers in Human Dynamics, 2024)
Can we conceive of a continuity in the way right-wing nationalisms address environmental issues from the origins of fascism to the currently ongoing global “polycrisis”? This article explores the use of the term “eco-fascism” in connection with the climate crisis and considers the political relationship between ecologism and the contemporary far right through a historical perspective, seeking to determine persisting patterns in the relationship between the far right and the environment. Section 1 travels back to the historical origins of this relationship between nationalism, fascism and the environment, arguing that the conceptions of nature adopted and nourished by fascism had scarcely anything to do with ecology in its contemporary meaning. Section 2 explores the most well-known and consolidated studies on the relationship between the far right and climate change denialism, identifying a broad consensus that unites scholars from various disciplines on the density, intensity and persistence of this political relationship in the current millennium. The article concludes by underlining the irreality, falsifiability and internal contradictions of the notion of “eco-fascism” at a time when right-wing regimes have seized power in many countries through the use of vocabularies and sentiments in defense of the territory and its resources, but with a substantial refusal to tackle global environmental problems.